2019
DOI: 10.3766/jaaa.17082
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and Speech Understanding in Noise: Auditory and Linguistic Factors

Abstract: Bilingual speakers often have difficulty understanding speech in noisy and acoustically degraded conditions.The first aim was to examine the potential source(s) of the difficulties that English-proficient bilingual listeners experience when hearing English speech in noise. The second aim was to assess how bilingual listeners perform on a battery of central auditory processing tests.A mixed design was used in this study.Normal-hearing college students (n = 24) participated in this study. The bilingual participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Instead of relying on one type of speech stimulus, we included two types to reflect the perception of the individual. This was done because previous studies have shown that bilinguals show more difficulty in noise as the linguistic complexity of the task increases [ 7 , 17 , 61 67 ]. Here, to evaluate the relation between physiology and perceptual measures, we combined the perceptual accuracy of the individual in both wordlists and sentences to reflect the perceptual performance in general, regardless of the effect of task complexity on performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of relying on one type of speech stimulus, we included two types to reflect the perception of the individual. This was done because previous studies have shown that bilinguals show more difficulty in noise as the linguistic complexity of the task increases [ 7 , 17 , 61 67 ]. Here, to evaluate the relation between physiology and perceptual measures, we combined the perceptual accuracy of the individual in both wordlists and sentences to reflect the perceptual performance in general, regardless of the effect of task complexity on performance.…”
Section: Methodsmentioning
confidence: 99%
“…One challenging listening condition that deteriorates speech perception is background noise [ 1 3 ]. It is well-known that speech perception in the presence of background noise can be more challenging for bilinguals compared to monolinguals [ 4 16 ] and that this disadvantage is present even when bilinguals have early exposure and strong proficiency in both languages [ 7 , 16 , 17 ]. At the same time, the literature notes the advantages of bilingualism for brain structure and function (e.g., [ 18 , 19 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Bilinguals previously were shown to have enhanced inhibitory control (Bialystok, 2011(Bialystok, , 2015 and subcortical encoding of the F0 of speech (Krizman et al, 2012;Skoe et al, 2017), processes that are fundamental to understanding speech in noise. Despite these advantages, bilinguals perform more poorly on clinical tests of speech-in-noise recognition (Shi, 2010(Shi, , 2012Lucks Mendel and Widner, 2016;Krizman et al, 2017;Skoe and Karayanidi, 2019). In this study, by assessing bilinguals and monolinguals on a selective attention task, a type of speechin-noise task that calls upon auditory processing and executive control, we could determine whether bilingual cognitive and sensory enhancements have benefits for everyday listening situations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature, however, has found bilinguals struggle in this realm relative to monolinguals (Mayo et al, 1997;Cooke et al, 2008;Lecumberri et al, 2011;Lucks Mendel and Widner, 2016;Krizman et al, 2017;Morini, 2020). Despite bilinguals' cognitive and sensory enhancements, they perform more poorly than monolinguals on clinical assessments of listening to speech in noise (Shi, 2010(Shi, , 2012Stuart et al, 2010;Krizman et al, 2017;Skoe and Karayanidi, 2019). Interestingly, this perception-innoise disadvantage only manifests when the target is linguistic; bilinguals instead show an advantage when the target is nonlinguistic (i.e., a tone; Krizman et al, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…Whilst highly valuable research tools, these tests require substantial time and resource to develop and validate. For this reason a single test, once developed, is often utilized for many decades [1,12]. This facilitates comparison of current results to previous research and the normative values for the original test [13].…”
Section: Introductionmentioning
confidence: 99%